2015
DOI: 10.3389/fpsyg.2015.00125
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the motivational behavior of pupils during outdoor science teaching within self-determination theory

Abstract: This paper presents data from a mixed-method pilot study (n = 84) searching into learning psychological aspects of an outdoor science teaching program. We use data from qualitative explorations into the pupils' learning motivation during field observation, a group interview, and open questionnaires, in order to understand quantitative measures from the Self-Determination Index (SDI), and the Practical Orientation (PO) of the program. Our data suggest that lower self-regulated pupils in “normal” science classes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 54 publications
(66 reference statements)
0
53
0
10
Order By: Relevance
“…In our study, those findings seem to hold true for ECBD students specifically, suggesting outdoor EE can help teachers supplement science instruction for all students using a single approach. Additionally, outdoor EE has been shown to positively impact science interest and efficacy (Mohr-schroeder et al, 2012;Hiller and Kitsantas, 2014;Dettweiler et al, 2015). As nature of science, science efficacy and science grades appeared to remain stable in both treatment and control groups, outdoor EE instruction appears just as effective for students with ECBDs as classroom instruction in maintaining these measures.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In our study, those findings seem to hold true for ECBD students specifically, suggesting outdoor EE can help teachers supplement science instruction for all students using a single approach. Additionally, outdoor EE has been shown to positively impact science interest and efficacy (Mohr-schroeder et al, 2012;Hiller and Kitsantas, 2014;Dettweiler et al, 2015). As nature of science, science efficacy and science grades appeared to remain stable in both treatment and control groups, outdoor EE instruction appears just as effective for students with ECBDs as classroom instruction in maintaining these measures.…”
Section: Discussionmentioning
confidence: 97%
“…Science instruction in US classrooms is rarely situated in the outdoors, despite the noted benefits in both cognitive and affective domains for students when they learn outside (Rickinson et al, 2004;Dyment, 2005;Carrier et al, 2013Carrier et al, , 2014Fägerstam and Blom, 2013;Rios and Brewer, 2014). Research on EE programming has found that science efficacy, science knowledge, and science achievement improve for all students after the experience (Tamir, 1991;Hiller and Kitsantas, 2014;Saribas et al, 2014;Dettweiler et al, 2015;Ardoin et al, 2017). Accordingly, outdoor EE may work to decrease indicators of ECBD (e.g., short attention spans and disruptive behaviors) as well as enhance learning, especially in science.…”
Section: Introductionmentioning
confidence: 99%
“…Pupils and teachers in this study commented on increased engagement with learning in the outdoors and overall school engagement. Research has demonstrated the ability of the natural environment to promote a desire to learn[35] and a positive relationship between learning and school motivation[39]. Teachers in our study suggested pupils’ learning was facilitated through the experiential pedagogy of outdoor learning.…”
Section: Discussionmentioning
confidence: 68%
“…A természettudományos tantárgyak tanulásában jelentkező problémák világszerte ismertek: a tanulók természettudományos érdeklődésének és motivációjának romlása számos országban jelent komoly gondot. A tantárgyak iránti érdeklő-désnek és a tanulási kedvnek döntő hatása van a továbbtanulás és a munkavállalás irányá-nak megválasztásában, ezért az említett problémák a pályaválasztási mutatókban is determináltak: egyre kevesebben választják a reál tárgyakhoz kötődő tudományos munkát hivatásukként (Braund & Reiss, 2006;Dettweiler, Ünlü, Lauterbach, Becker, & Gschrey, 2015;Rocard et al, 2007). A tanulási motiváció és a tantárgyi attitűdök növelésének ezért az oktatásban nagyobb hangsúlyt kell kapnia.…”
unclassified
“…Az iskolai környezetnek és légkörnek kritikus szerepe van a tanulók tanulási kedvének, motivációjának alakulásában, és ennek javí-tásában szerepet kaphatnak az iskolán kívüli tanulás színterei is (Fägerstam & Blom, 2013;Demirci Güler & Afacan, 2013). Ugyanis az olyan informális tanulási környezetre jellemző oktatási módszerek, mint például a laboratóriumi vagy múzeumi tanulás, segítik a diákok autonómiáját a tanulási folyamatokban, kézzelfoghatóbbá teszik a tananyagot, ezáltal magasabb intrinzik motivációt generálva (Dettweiler et al, 2015). Növelhető általuk a tanulók tudományos érdeklődése, ami pozitívan befolyásolhatja a tudományos pályák iránti választási kedvet (Nazier, 1993; Rudman, 1994).…”
unclassified